2021
DOI: 10.51791/njap.v41i2.774
|View full text |Cite
|
Sign up to set email alerts
|

Responses of pubertal rabbits to dietary supplementation of ginger (Zingiber officinale rosc) rhizome powder

Abstract: Seventy two (72) sexed crossbred rabbits aged 6 months were used to determine the effect of ginger rhizome powder (GRP) supplementation on reproductive organ and serum sex hormonal characteristics of pubertal rabbits. The experimental rabbits were divided into 2 treatment groups comprising 36 males and 36 females. Each group was divided into 4 dietary treatments (BT1, BT2, BT3 and BT4 ) of 9 animals and replicated thrice with 3 animals per replicate in a completely randomized design (CRD). The animals were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
3
7
2
1
Order By: Relevance
“…The results of the present study were not in agreement with earlier studies (30,31) , which reported different mineral contents in ginger powder. In addition, the study of Prakash et al (15) showed that ginger powder contained 9⋅41 mg/100 g iron, 104⋅02 mg/100 g calcium and 204⋅02 mg/100 g phosphorous, of which calcium content was in accord to the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study were not in agreement with earlier studies (30,31) , which reported different mineral contents in ginger powder. In addition, the study of Prakash et al (15) showed that ginger powder contained 9⋅41 mg/100 g iron, 104⋅02 mg/100 g calcium and 204⋅02 mg/100 g phosphorous, of which calcium content was in accord to the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The ready-to-drink red ginger product contributed 59.308-64.418; 12.741-24.112; 0.102-0.279; and 48.961-52.651% of the red ginger powder product for ash, fat, protein, and carbohydrate contents, respectively. These results also align with research conducted by [29], which showed that ginger powder is very rich in ash content and followed by water content. The ash content illustrates the amount of mineral elements contained in ginger so that high ash content can indicate the content that is good for health.…”
Section: Proximate Compositionssupporting
confidence: 91%
“…The tea extract influenced the sodium content of the diet drink significantly ( p ≤ .05), which is due to the sodium content of tea extract that is, 0.09% being determined to be the maximum quantity of sodium content in black tea. On the other hand, herb extract also contributed significantly ( p ≤ .05) to the sodium content of DDs which might be due to the presence of sodium in a ginger root, that is, 38.96 μg/g (Ogbuewu et al, 2014). Tea extract concentration affects potassium content of DDs inversely (Table 3) owing to its contribution in tea, that is, 30,362 μg/ 100 ml (Klepacka et al, 2021).…”
Section: Resultsmentioning
confidence: 99%